An Effect Sensitivity Harmonics of Rotor Induction Motors Based On Fuzzy Logic - Aryza, Solly; Irwanto, Muhammad; Khairun Nizam, Wan; Lubis, Zulkarnain; Putri, Maharani; Ramadhan, Andri; Nova Hulu, Fitria; Wibowo, Pristisal; Novalianda, Sari; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
The stator is apart complicated because it is one of the main parts of mechanical components inside an induction motor and is often a heat problem in the electrical pressure and also due to competitive environmental conditions, etc. So this study discusses how the technique used in identifying the initial level of small error rate in the induction motor. Several studies also discuss motor vibration detection analysis. So this research is done about the harmonization of rotation causing this vibration amplitude which causes problems of mechanical stress and motor. So that the results of this research can be a result of learning about the effect of error amplitude, causing problems in the rotor and fuzzy logic results performed also resulted in increased amplitude of vibration in rotor harmonicsÂ Â Â